How Economics-Socio-Cultural Status affect Indonesian Students’ Performance in Mathematics? an Insight from PISA 2012-2022 - Setiawan, Ezra Putranda; Kismiantini, Kismiantini; Montesinos-López, Osval A. (FKIP Universitas Lampung, 2024)
How Economics-Socio-Cultural Status affect Indonesian Students’ Performance in Mathematics? an Insight from PISA 2012-2022. To date, the average mathematics performance of Indonesian students in PISA tends to be unchanged, and lower than that of OECD countries. However, PISA participants in Indonesia consist of students from five to six different grades. Objectives: This research aims to determine how Economic-Socio-Cultural Status (ESCS) and student grades influence Indonesian students' mathematics performance. Methods: We apply a quantitative approach using multiple linear regression analysis methods using the PISA 2012, 2015, 2018, and 2022 datasets. In this analysis, we also use the weight of each sample and the overall plausible value for mathematics performance. Findings: we found a significant relation between education level and ESCS regarding students' overall mathematics performance in PISA from 2012 to 2022. The interaction coefficient increases as the level increases from grade 8 of junior secondary school to grade 11. Conclusion: ESCS has a contribution to the diversity of students' mathematics performance at the same grade. From 2012 to 2022, the relative position of Indonesian students' ESCS compared to all participant has declined, although its influence on student mathematics performance tends to decline. Keywords: PISA, mathematics, Indonesia.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024122